Estimating tiger and its prey abundance in Bardia National Park, Nepal - Karki, J. B.; Jhala, Y. V.; Pandav, B.; Jnawali, S. R.; Shrestha, R.; Thapa, K.; Thapa, G.; Pradhan, N. M. B.; Lamichane, B. R.; Barber-Meyer, S. M. (Banko Janakari, 2016)
We estimated tiger and wild prey abundance in the Bardia National Park of Nepal. Tiger abundance was estimated from camera trap mark recapture in 85 days between December, 2008 to March, 2009 by placing 50 camera trap pairs in 197 trap locations with a sampling effort of 2,944 trap nights. We photo captured 16 individuals (≥1.5 year old) tigers identified on the basis of their unique stripe patterns. The number and density (per 100 km2) of tiger was 19 (SE 3.3) and 1.31 (SE 0.32), respectively. Distance sampling was used to assess the prey abundance on 170 systematically laid line transects between May–June, 2009. The density of all the wild prey (individuals/km2) was 56.3 (SE 6.5). The density (individuals/km2 Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page: 60-69, 2016